Rapidly Fatal Postlaparoscopic Liver Infection from the Rarely Isolated Species Clostridium butyricum - Kenneth L. Muldrew (Case Reports in Infectious Diseases)
We report a case of a rapidly fatal postlaparoscopic cholecystectomy liver infection from the rarely isolated species Clostridium butyricum. Liver examination at autopsy showed cystic spaces, necrosis, and spore-forming Gram-positive rods. 16sRNA gene sequencing of the cystic liver tissue identified the organism as C. butyricum.